Intentions of Patients With Cancer and Their Relatives to Use a Live Chat on Familial Cancer Risk: Results From a Cross-Sectional Web-Based Survey - Paula Memenga; Eva Baumann; Hanna Luetke Lanfer; Doreen Reifegerste; Julia Geulen; Winja Weber; Andrea Hahne; Anne Müller; Susanne Weg-Remers (JMIR Publications, 2023)
BackgroundAn important prerequisite for actively engaging in cancer prevention and early detection measures, which is particularly recommended in cases of familial cancer risk, is the acquisition of information. Although a lot of cancer information is available, not all social groups are equally well reached because information needs and communicative accessibility differ. Previous research has shown that a live chat service provided by health professionals could be an appropriate, low-threshold format to meet individual information needs on sensitive health topics such as familial cancer risk. An established German Cancer Information Service is currently developing such a live chat service. As it is only worthwhile if accepted by the target groups, formative evaluation is essential in the course of the chat service's development and implementation. ObjectiveThis study aimed to explore the acceptance of a live chat on familial cancer risk by patients with cancer and their relatives (research question [RQ] 1) and examine the explanatory power of factors associated with their intentions to use such a service (RQ2). Guided by the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2), we examined the explanatory power of the following UTAUT2 factors: performance expectancy, effort expectancy, social influence, facilitating conditions, and habit, supplemented by perceived information insufficiency, perceived susceptibility, perceived severity, and cancer diagnosis as additional factors related to information seeking about familial cancer. MethodsWe conducted a cross-sectional survey via a German web-based access panel in March 2022 that was stratified by age, gender, and education (N=1084). The participants are or have been diagnosed with cancer themselves (n=144) or have relatives who are or have been affected (n=990). All constructs were measured with established scales. To answer RQ1, descriptive data (mean values and distribution) were used. For RQ2, a blockwise multiple linear regression analysis was conducted. ResultsOverall, 32.7% of participants were (rather) willing, 28.9% were undecided, and 38.4% were (rather) not willing to use a live chat on familial cancer risk in the future. A multiple linear regression analysis explained 47% of the variance. It revealed that performance expectancy, social influence, habit, perceived susceptibility, and perceived severity were positively associated with the intention to use a live chat on familial cancer risk. Effort expectancy, facilitating conditions, information insufficiency, and cancer diagnosis were not related to usage intentions. ConclusionsA live chat seems promising for providing information on familial cancer risk. When promoting the service, the personal benefits should be addressed in particular. UTAUT2 is an effective theoretical framework for explaining live chat usage intentions and does not need to be extended in the context of familial cancer risk.